Advances in hydrogel-based materials for breast cancer bone metastasis: from targeted drug delivery to bone microenvironment remodeling - Chen, Jiayi; Ma, Jun; Xu, Zhuoming; Luo, Huanhuan; Qian, Chenhong (Frontiers in Pharmacology, 2025)
Breast cancer has become the most common malignant tumor in women around the world, and bones are the most common part of all metastatic breast cancers. Breast cancer bone metastasis (BCBM) is the main cause of death in patients with advanced breast cancer. It is still mainly clinically palliative treatment, with problems such as systemic toxicity, low target specificity, and insufficient bone repair. Therefore, there is an urgent need to develop new therapeutic strategies to overcome these challenges. This review summarizes recent advances and innovative applications of smart hydrogel-based delivery systems for breast cancer bone metastasis, highlighting their significant potential in gene delivery and immune microenvironment remodeling. Current limitations and future research directions are also discussed.